The Fundamentals of Respiratory Physiology to Manage the COVID-19 Pandemic: An Overview - Allado, Edem; Poussel, Mathias; Valentin, Simon; Kimmoun, Antoine; Levy, Bruno; Nguyen, Duc Trung; Rumeau, Cécile; Chenuel, Bruno (Frontiers in Physiology, 2021)
The growing coronavirus disease (COVID-19) crisis has stressed worldwide healthcare systems probably as never before, requiring a tremendous increase of the capacity of Intensive Care Units to handle the sharp rise of patients in critical situation. Since the dominant respiratory feature of COVID-19 is worsening arterial hypoxaemia, eventually leading to acute respiratory distress syndrome (ARDS) promptly needing mechanical ventilation, a systematic recourse to intubation of every hypoxemic patient may be difficult to sustain in such peculiar context and may not be deemed appropriate for all patients. Then, it is essential that caregivers have a solid knowledge of physiological principles to properly interpret arterial oxygenation, to intubate at the satisfactory moment, to adequately manage mechanical ventilation and finally, to initiate ventilator weaning, as safely and as expeditiously as possible, in order to make it available for a next patient. Through the expected mechanisms of COVID-19-induced hypoxaemia, as well as the notion of silent hypoxaemia often evoked in the COVID-19 lung injury and its potential parallelism with High Altitude Pulmonary Edema, from the description of hemoglobin oxygen affinity in patients with severe COVID-19 to the interest of the prone positioning in order to treat severe ARDS patients, this review aims to help caregivers from any speciality to handle respiratory support following the recent knowledge in pathophysiology of respiratory SARS-CoV-2 infection.